Cobalt supported on Zirconia. Selective catalytic reduction of NO using propane as reducing agent (2014)
ABSTRACT: The catalytic behavior of a series of cobalt catalysts supported on zirconia in the selective catalytic reduction (SCR) of NO has been studied using propane as reducing agent. The catalysts were characterized by Raman Spectroscopy, Temperature Programmed Reduction (TPR), Diffuse Reflectance Spectroscopy UV-Vis (DRS) and X-ray Photoelectron Spectroscopy (XPS) to assess the physicochemical properties of cobalt species. Results for SCR of NO indicate that the activity is substantially related to the cobalt concentration and consequent nature of supported cobalt species. The formation of segregated oxidic phases on the catalytic surface produces an activity decrease. The most active catalyst contains Co(II) ions, interacting with the support, in tetrahedral coordination